The impact of implementing a preprinted order form for inpatient management of otherwise healthy children admitted to a tertiary care centre with a diagnosis of bronchiolitis. Issue 8 (7th January 2019) - Feder, Joshua; Bijelic, Vid; Barrowman, Nick; McDonald, Jaime; Murchison, Barbara; Jetty, Radha; Tjahjadi, Anindita; Parker, Kristy; Pothos, Mary; Pound, Catherine M
Abstract: Objective: To examine the effect on length of stay (LOS) of a preprinted order (PPO) set for children admitted to hospital with a diagnosis of bronchiolitis, as well as on quality improvement measures, medical errors, and resource utilization. Patients and methods: A retrospective chart review was performed of children admitted to the inpatient units at the Children's Hospital of Eastern Ontario (CHEO) with a discharge diagnosis of bronchiolitis. Primary and secondary outcomes were compared between the pre-PPO (December 1, 2014 to June 30, 2015) and post-PPO (December 1, 2015 to June 30, 2016) periods. The primary outcome was LOS in days. Secondary outcomes included the proportion of quality improvement measures reached, the number of medical errors, and resource utilization. Results: A total of 245 patients were included; 122 patients from the pre-PPO period (December 1, 2014 to June 30, 2015) and 123 patients from the post-PPO period (December 1, 2015 to June 30, 2016). Mean LOS was 3.1 days (2.7 to 3.5 days) and 2.8 days (2.4 to 3.2 days) in the pre- and post-PPO periods, respectively (multivariate analysis, P-value = 0.13). There were significant differences between the pre- and post-PPO periods in a number of quality improvement measures, although not in the number of medical errors. Significant reductions in oxygen, corticosteroid, antibiotic, and bronchodilator use were noted post-PPO implementation. Conclusion: Although our bronchiolitis PPO did not significantly shorten LOS, it led to important improvements in quality improvement measures and in resource utilization efficiency.